THE IMPLEMENTATION OF THE LUDER CONTINGENCY MODEL IN PUBLIC SECTOR ACCOUNTING REFORMS IN INDONESIA - Arni Karina; Syamsudin; Muhammad Nur; Kumba Digdowiseiso; Siti Nurain Muhmad (RADJA PUBLIKA, 2023)
This research originated from the necessity to gain a comprehensive comprehension of the determinants that impact the achievement of public sector accounting reform, particularly in the Indonesian context. The objective of this study is to investigate the application of the Luder Contingency Model in the specific context of public sector accounting reform in Indonesia. The employed approach entails a Systematic Literature Review, which involves scrutinizing diverse relevant research, encompassing the Luder Contingency Model theory and its implementation in the public sector. The research findings indicate that societal pressure and the demands of globalization are significant factors in promoting public sector accounting reform in Indonesia. The success of reform is influenced by social structural variables of information users, such as their information needs and level of interest in accounting information. Similarly, the attributes of political administration/information providers, such as governance systems and organizational culture, are crucial in facilitating transparency and accountability. Nevertheless, the presence of obstacles in the form of restricted resources and absence of political backing presents significant difficulties. To summarize, while there has been some advancement in the implementation of the Luder Contingency Model, additional endeavors are required to enhance public awareness, allocate sufficient resources, and garner robust political backing in order to achieve successful public sector accounting reform in Indonesia.